Specificity studies on cytotoxic thymus-derived lymphocytes reactive with influenza virus-infected cells: evidence for dual recognition of H-2 and viral hemagglutinin antigens. - Ennis, F A (1977)
Cytotoxic thymus-derived (T) lymphocytes were readily detected in spleens of mice inoculated intranasally with mouse-adapted A/Port Chalmers (H3N2), A/England (H3N2), A/PR/8 (H0n1), and B/Hong Kong influenza viruses. T-cell-mediated lysis of H-2 compatible target cells infected with the strain of virus used to immunize the mice was considerably higher than lysis of either syngeneic cells infected with a different strain of influenza virus or allogeneic cells infected with the immunizing strain of influenza virus. The findings that cytotoxic lymphocytes can distinguish minor antigenic variants among influenza viruses and that lysis depends on H-2 histocompatibility between lymphocyte and target cell support the concept of dual recognition of visual and H-2 histocompatibility antigens in T-cell-mediated antiviral immunity.